Intellectual Heritage and Institutional Collective Memory: a case study in the scientific framework of the Institute of Physics of the Federal University of Rio de Janeiro - IF UFRJ - Teixeira, Robson da Silva (2024)
The theme of the article in the context of the field of Museology, involves Intellectual Heritage and Institutional Collective Memory interpreted as a cultural asset and constructed through the scientific production of professors at the Institute of Physics of the Federal University of Rio de Janeiro – IF UFRJ. The article aims to identify and quantify the scientific production of these IF UFRJ professors in their context of memorialistic-heritage experiences. The methodology used was bibliographical research and involved activities related to applied methods and techniques, supported by documental and primary sources. The results relate specialized contents of Museology, Institutional Memory, Intellectual Heritage and the field of Physics. And they pointed out that the institution's researchers produced, in 2020, 335 scientific articles, published in several scientific journals. It is concluded that framing the teaching production as an intangible asset integrated into the institution's Virtual Museum was a necessary and relevant action, because the scientific production of the research subjects are part of the Cultural Heritage of Science, since they represent a form of knowledge transmission, values and experiences from one generation to another, and representative of an adequate element for the musealization process in a referential context of memory, of heritage in an internet environment.